2004
DOI: 10.1002/adsc.200303239
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Amino Diols Mediated by Homogeneous and Heterogeneous TEMPO

Abstract: The conversion of amino diols to aminohydroxy acids by oxidation of the primary hydroxy group mediated by homogeneous and heterogeneous TEMPO (2,2,6,6-tetramethylpiperidine 1-oxyl radical) is reported. The synthesis uses NaOCl as primary oxidant and TEMPO, either dissolved in the homogeneous phase or entrapped in a sol-gel matrix, as catalytic mediator. Homogeneous TEMPO is suitable for the oxidation of aliphatic methylamino diols, while the hybrid organic-inorganic silica sol-gel catalysts are more selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 22 publications
0
19
0
2
Order By: Relevance
“…>95:5). Deprotection of the MOM group followed by chemoselective oxidation of the primary alcohol to the acid [39][40][41] in the presence of the secondary alcohol afforded hydroxyphthioceranic acid 10, the target natural product, in 90% isolated yield (Fig. 5).…”
Section: Resultsmentioning
confidence: 98%
“…>95:5). Deprotection of the MOM group followed by chemoselective oxidation of the primary alcohol to the acid [39][40][41] in the presence of the secondary alcohol afforded hydroxyphthioceranic acid 10, the target natural product, in 90% isolated yield (Fig. 5).…”
Section: Resultsmentioning
confidence: 98%
“…This compound was obtained by generating 4-nitrobenzoic acid cyclocondensed with unchanged (1S,2S)-ANP in the reaction system. The conversion of (1R,2R)-ANP to (1R,2R)-α-amino-β-hydroxy acid (36) by oxidation of the primary hydroxyl group mediated by homogeneous and heterogeneous 2,2,6,6-tetramethyl piperidine 1-oxyl radical (TEMPO) was reported by Pagliaroa [60]. Studies showed that heterogeneous TEMPO (the hybrid organic-inorganic silica sol-gel catalysts) is a selective mediator of the oxidation of benzylic amino diols.…”
Section: Applications In Oxidation Reactionsmentioning
confidence: 97%
“…The use of the homogeneous catalyst resulted in the unselective degradation of the targeted acids, thereby showing an additional benefit of the immobilization strategy. [102] Silica-supported TEMPO was used in transition-metal-free aerobic oxidation reactions of alcohols, [53] and the electrochemical regeneration of silica-immobilized TEMPO was also reported to be feasible. [83c] Two different silica-supported TEMPO systems have been used industrially and were introduced under the trade names SilicaCat TEMPO [103] and FibreCat TEMPO.…”
Section: Immobilized Nitroxides As Reusable Catalysts In Oxidationsmentioning
confidence: 99%